Vaccination for COVID-19 among historically underserved Latino communities in the United States: Perspectives of community health workers - Garcini, Luz M.; Ambriz, Arlynn M.; Vázquez, Alejandro L.; Abraham, Cristina; Sarabu, Vyas; Abraham, Ciciya; Lucas-Marinelli, Autumn K.; Lill, Sarah; Tsevat, Joel (Frontiers in Public Health, 2022)
A critical step to reduce the spread of COVID-19 is vaccination. We conducted a mixed methods project that used online surveys and focus groups with 64 Community Health Workers and Promotor/as (CHW/Ps) located near the U.S.-Mexico border to identify barriers and facilitators to COVID-19 vaccination among Latino communities that have been historically underrepresented and medically underserved. Overall, personal barriers to vaccination included mistrust of manufacturers and administrators as well as fear of: becoming infected from the vaccine, discrimination/stigmatization from healthcare professionals administering the vaccine, exploitation/manipulation by the government or health authorities, and having personal information mishandled. Environmental and community barriers included being undocumented and fear-inducing myths and beliefs. Additional barriers included limited information and logistics pertaining to vaccination access. Targeted efforts are needed to overcome barriers in a culturally and contextually sensitive manner to prevent harm and reduce risk of infection among communities that have been historically underrepresented.